Spatial Analysis of Land Surface Temperature in Dhaka Metropolitan Area - Raja, Debasish Roy (Journal of Bangladesh Institute of Planners, 2012)
The research is carried out to assess the relationship between the land surface temperatures (LST) and land cover (LC) changes both in quantitative and qualitative ways in Dhaka Metropolitan Area (DMA) using Landsat TM/ETM+ data over the period 1989 to 2010. Supervised classification methods have been taken to prepare the LC map. LST is derived from the thermal band of Landsat TM/ETM+ using the calibration of spectral radiance and emissivity correction of remote sensing. GIS based spatial simulation has been conducted to establishing this relationship using NDBI and NDVI. The changing of LST is directly correlated with LC transition. LST is increasing in those areas where urban developments have been concentrated over this period. Besides, the amount of Vegetation (NDVI) is negatively correlated with LST. The trend of the LST and LC transition indicates that LST will be abruptly increased in the near future and it will affect on micro climate. The urban LST maps, the analyses of thermal-land cover relationships and the spatial simulated figure could be used as a guideline for urban planning, strategies for quality improvement of urban environment and a smart solution to the reduction of UHI effect. Journal of Bangladesh Institute of Planners, Vol. 5, Dec 2012, pp. 151-167